INCLUSIVE EDUCATION AS A FULFILLMENT OF INDONESIAN CULTURE - Mhd. Syafii (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research aims to explore the implementation of inclusive education in elementary schools in Indonesia through a qualitative approach. Inclusive education in Indonesia, which requires students with and without disabilities to learn together in the same environment, still faces various challenges in its implementation. This research uses in-depth interviews, participant observation, and case studies to collect data from various stakeholders, including teachers, students, and parents, in several elementary schools in urban and rural areas. Research findings show that although there is increasing awareness of the importance of inclusive education, the main challenges faced are a lack of training for teachers, limited facilities and infrastructure, and gaps in understanding of the concept of inclusion itself. On the other hand, the research results also show the positive impact of inclusive education on the social and emotional development of students, both those with disabilities and those without. Students with disabilities showed improvements in social interactions, while students without disabilities became more empathetic towards their peers with special needs. This research suggests the need to increase training for teachers, provide adequate facilities, and increase community and school awareness about the importance of implementing effective inclusive education.